Unicentric castleman’s disease of neck node in old age- rare presentation of a rare disease - Gopalakrishnan Midhun. P.; Nizarudeen A. (International Journal of Medical Research and Review, 2017)
Castleman’s disease is an uncommon lymphoproliferative disorder that may be unicentric or multicentric disease. We are reporting a case of 75 year old female presented with left level 3 cervical lymph node, whose final diagnosis was unicentric castleman’s disease. This presentation is uncommon because unicentric castleman’s disease is usually seen in younger adults and it usually affects lymph nodes in chest or abdomen. People with localized Castleman’s disease are usually cured by surgical removal of the affected lymph nodes.